2016
DOI: 10.11648/j.ijdm.20160202.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Frequency of Errors in Conventional Panoramic Radiographs

Abstract: Although use of conventional panoramic systems leads to degrade the image quality, it is still common in Sri Lanka. The objective of the study was to determine the frequency of errors occurred during Ortho Pantomo Graph (OPG) and to minimize the further occurrence. Two hundred and fifty OPGs were collected from Department of Radiology, Dental Hospital (Teaching) Peradeniya (DHTP). Quality of 250 OPGs was evaluated by one radiologist and a radiographer. Evaluators assessed all 250 radiographs for presence of er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…As many as 233 of the 495 panoramic radiographs had this error (47.07%). The results of this study are similar to most research results that have stated that the most common error found was improper tongue position [18,19]. A categorical comparative analysis test was conducted using Pearson's c 2 to see if there was a significant difference between the errors in incorrect tongue position in children, adults, and the elderly.…”
Section: Discussionsupporting
confidence: 84%
“…As many as 233 of the 495 panoramic radiographs had this error (47.07%). The results of this study are similar to most research results that have stated that the most common error found was improper tongue position [18,19]. A categorical comparative analysis test was conducted using Pearson's c 2 to see if there was a significant difference between the errors in incorrect tongue position in children, adults, and the elderly.…”
Section: Discussionsupporting
confidence: 84%